Vocabulary Thresholds Study for Business English Major Based on the Range Corpus - Wang Run; Li Weina (Ilmu Inovasi Nusantara, 2024)
The texts have been selected from 45 articles of 15 units of Selected Readings of Business English and from prominent economic English newspapers in China and the United States—China Economic Net and The Economist. Employing the vocabulary corpus software, Range32, we conducted a statistical examination of vocabulary coverage and the frequency of corresponding terms in the British National Corpus (BNC). This rigorous analysis aims to ascertain whether the content of the textbook aligns with the requisites of specific professional tests. Additionally, it serves to assist students and learners of Business English in China by aiding them in identifying suitable English-language reading materials. This research provides a valuable reference, guiding individuals toward reading newspapers that align with their vocabulary proficiency in English. The study findings indicate that to attain a fundamental comprehension of the reading materials, achieving a 95% vocabulary coverage requires a command of 4,000 to 5,000 vocabulary words for Selected Readings of Business English, 4,500 to 5,000 vocabulary words for China Economic Net, and 5,000 to 6,000 vocabulary words for The Economist. For a more fluent reading experience, corresponding to a 98% vocabulary coverage, a mastery of 7,500 to 8,000 vocabulary words is necessary for Selected Readings of Business English, 8,500 to 9,000 vocabulary words for the China Economic Net, and 10,000 to 11,000 vocabulary words for The Economist. And this study suggests that the vocabulary thresholds for Business English majors should be 4,000 to 6,000 (95% vocabulary coverage) and 8,000 to 11,000 (98% vocabulary coverage)